BIOLOGIA FORENSE NA ESCOLA: APLICAÇÃO DE ATIVIDADE INTERATIVA PARA ALUNOS DO ENSINO BÁSICO - ANDRADE, Raul de Lima Soares; VASCÃO, Andressa Aparecida Xavier; MILITÃO, Fernanda Turini; ALVES, Jonilda da Silva; SILVA, Vitória Aires; MORAIS, Glaucia de Almeida (ANAIS DO ENIC, 2023)
-